Knowledge, attitude and practice on COVID-19 among students during the early phase of pandemic in a university in Borneo, Malaysia - Mohd Fazeli Sazali; Syed Sharizman Syed Abdul Rahim; Mohd Haazik Mohamed; Azizan Omar; Pang, Nicholas Tze Ping; Mohammad Saffree Jeffree; Yeap, Boon Tat; Nelbon Giloi; Farhana Harzila Mohd Bahar; Wiwik Afridah; Abdul Hakim Zakkiy Fasya; Mohd Rohaizat Hassan; et al. (PagePress Publications, 2021)
Background: COVID-19 related knowledge, attitude and practice plays a major role in determining the readiness of the community to adopt the behavioural change towards recommended preventive measures outlined by public health officials. This study aims to assess the knowledge, attitude, and practice regarding COVID-19 among university students as well as its associated factors. Method: This is a cross sectional study that was conducted among students in a public university during the early phase of COVID-19 pandemic in Malaysia. An online validated self-administered questionnaire was used to collect the data. Mann-Whitney U and Kruskal Wallis test was used to determine the association between independent variables with knowledge, attitude, and practice score. Results: Overall response rate of this study was 92.9 (n=524). Median score of knowledge domain was 78.0 (IQR= ±12.0), median attitude score of 49.0 (IQR= ±5.0), and median practice score of 80.0 (IQR= ±11.0). The mean knowledge, attitude and practice score were significantly higher among diploma holder (vs degree holder, p<0.05), residing in main Kota Kinabalu campus (vs non-KK campus, p<0.001), studying in medical faculty (vs non-medical faculty, p<0.001), and attended COVID-19 education (vs non-attendance; p<0.05). Conclusion: COVID-19 related knowledge and attitude were below satisfactory level during earlier phase of the pandemic. However, majority of respondents have positive behaviour towards COVID-19 prevention. This highlights the importance of accurate and tailored health education to improve the level of knowledge, attitude and practice of recommended measures to prevent COVID-19 spread.